Activity of Antimicrobial Combinations Against Extensively Drug-Resistant Acinetobacter baumannii as Determined by Checkerboard Method and E-test - Sunee Limsrivanichakorn; Popchai Ngamskulrungroj; Amornrut Leelaporn (Siriraj Medical Journal, 2020)
Objective: Combination therapy is needed to treat extensively drug-resistant (XDR) Acinetobacter baumannii infection. Colistin (Col) in combination with another drug is usually used for that purpose. The aim of this study was to determine the activity of antimicrobial combinations against XDR A. baumannii using both standard checkerboard (CB) method and E-test. E-test was also evaluated for application in a diagnostic bacteriology laboratory by comparing its efficacy with that of CB method. Methods: Eighty clinical isolates of XDR A. baumannii were used to determine the activity of the following antimicrobial combinations by CB method and E-test: Col+cefoperazone/sulbactam (Cps), Cps+moxifloxacin (Mox), and Col+Mox. Comparison of CB and E-test was also evaluated. Results: By CB method, Col+Cps yielded a synergistic effect rate (12.5%) higher than those of the other 2 combinations (CpS+Mox 5% and Col+Mox 0%). The majority of test results revealed additivity. Col+Cps, Cps+Mox, and Col+Mox exhibited additive effect against 78.75%, 85.0%, and 87.5% of isolates, respectively. Overall, E-test and CB yielded only 37.5% concordant rates. However, high concordant rates were specifically observed in additive effect of Col+Cps (73.8%) and Cps+Mox (80.4%). Conclusion: Col+Cps exhibited better activity than the other two combinations against XDR A. baumannii. E-test is the method that should be used, but its use is limited to the additive results of Col+Cps and Cps+Mox.